Transcatheter aortic valve implantation in patients with anomalous coronary artery. Issue 2 (14th January 2023) - Bajoras, Vilhelmas; Diečkus, Laurynas; Wong, Ivan; Laurinavičienė, Anna; Davidavičius, Giedrius; Čėsna, Sigitas
Abstract: Objectives: The aim of this review was to analyze literature and provide systematic algorithm to guide decision making during TAVI procedure. Background: Transcatheter aortic valve implantation (TAVI) is growing in popularity and expanding to younger patients with lower risk profiles. Currently, there is no concise guideline on the management strategy during TAVI in patients with anomalous coronary artery (ACA) anatomy undergoing this procedure. Methods: A systematic search was conducted for relevant case reports of TAVI in patients who had confirmed ACA anatomy. Twenty‐four case reports, that met the criteria for this review, were identified and included in the final study size. Results: TAVI was successful in 23 out of 24 cases. Half of the cases (12) described performing balloon aortic valvuloplasty (BAV) before TAVI. The majority (15) reported using angiogram Postimplantation. Only one‐third of cases (8) reported performing coronary protection (with either wire, wire and stent or wire and balloon). Two‐third of case reports (16/24, 67%) mentioned using Edwards SAPIEN balloon expandable transcatheter heart valves (THV). Conclusions: Preprocedural diagnostic imaging tests play important role in determining the ACA anatomy and its relation to the aortic valve. BAV with simultaneous coronary arteries angiography or aortography should be performed before implantation of THV, as it could potentially predict whether the ACA would be compressed. Using at least a coronary wire for ACA protection is recommended in case there is high risk of ACA obstruction. Management strategy should be individualized when performing TAVI in patients with ACA.